Peer Foster Student Program in the Formation of Character Value Gotong royong Students in School - Argadinata, Hasan; Imron, Ali; Sumarsono, R. Bambang (International Journal of Education, 2021)
The purpose of this study is to find out the strategy of the character-building mutual character of students through the Peer FosterIng Student program. To answer the topic raised, researchers chose the study using a qualitative approach because researchers want to know in-depth about the phenomenon that actually occurs in schools. In the process of analyzing data, researchers used the help of the NVivo program to find the output of data reduction, field records, and documentation studies. Peer Foster Student Program (PFS) itself is a movement to build awareness among students in Banyuwangi. The management is done from students, by students, and for students in the school. Assistance programs were between students to foster a sense of care and divided love. This activity was carried out by the establishment of a group of managers from students to raise voluntary funds from all students in the school that will be distributed to the recipient students in the form of school supplies. The formation of mutual character values through peer foster student programs is carried out by fostering the value of caring, helping, responsible, cooperative, helping to achieve common welfare goals. Through this program, the value of gotong royong (communal work) character is seen and becomes an essential concern for the future provision of learners when plunged directly into the vast ocean in public life.